Development of a non-human primate model for preclinical research of a novel auditory nerve implant - Sondh, Inderbir; Johnson, Luke A.; Ghose, Geoffrey M.; Loveland, Aaron; Larson, Lisa; Lim, Hubert H.; Adams, Meredith E. (Frontiers in Neuroscience, 2025)
The cochlear implant is a widely available hearing restoration technology that can provide speech understanding in quiet environments. This technology struggles however, in noisy settings or situations involving multiple speakers. The primary cause of these performance limitations is a poor neural interface, in which the bony wall of the cochlea separates the electrode surface from the auditory nerve fibers, thus causing unwanted current spread and non-specific frequency activation. This study utilizes an alternative auditory prosthetic technology (auditory nerve implant, ANI) that enables direct auditory nerve stimulation, which provides a potentially superior neural interface and enables more precise targeting of auditory nerve fibers than traditional cochlear implants. As auditory nerve implants progress towards clinical translation, new implant designs and stimulation strategies will be created. Animal models to efficiently test and iterate through these new designs will be useful for the continued development of ANI technology. We present a viable surgical approach in the non-human primate (rhesus macaque) along with electrophysiological results that demonstrate robust activation of the auditory system at low current levels via intraneural stimulation. Our findings indicate that the rhesus macaque, which possesses an inner ear anatomy more similar to the human compared to other animal models used in the hearing field (e.g., rodents, felines and ferrets), has strong potential as a useful preclinical testbed involving an upright head model for future ANI prototypes and stimulation strategy development.